The Influence of Product Quality and Service Quality on Customer Loyalty Through Customer Satisfaction - Aji, Rangga Aji Saputra; R A Nurlinda (PT Inovasi Pratama Internasional, 2024)
Product quality an important role in the marketing strategy that can be implemented by Informa by providing the best products for its consumers to provide trust, satisfaction and a positive experience so that consumers make product purchases in the future. The purpose of this study was to determine the greatest influence of customer loyalty. This type of research is quantitative with a purposive sampling technique distributed through a questionnaire to 190 male and female respondents of Informa product customers aged 17-50 years who have made a purchase at least 1 time in the last 1 year and domiciled in Jakarta. Primary data analysis was carried out using the SEM Smart PLS method. The results of this study indicate that product quality and service quality have an effect on customer satisfaction. Furthermore, product quality and service quality have a direct effect on customer loyalty, but satisfaction does not affect customer loyalty. Customer satisfaction is not proven to be a mediation between product quality and service quality on customer loyalty. This study contributes to Informa in maintaining and increasing customer loyalty, which can be seen from several factors formed from each consumer complaint optimally and measurably. For further research, the researcher suggests expanding the research area and looking for objects in other fields.